Urban development on the Island of Mozambique: Socio-spatial challenges in contexts of conservation of built heritage: Desafios sócio-espaciais em contextos de conservação do património edificado (Publicatio UEPG: Ciências Sociais Aplicadas, 2023)
This article under the theme “urban development on the Island of Mozambique: socio-spatial challenges and contexts of conservation of the built heritage”, aims to reflect on the challenges of urban development on the Island of Mozambique, as a World Heritage Site, which carries with it a set of historic buildings. The research problematizes the influence of the built heritage for the urban development of the city, with emphasis on the City of Macuti. The methodology adopted for the elaboration of the article was of a qualitative approach, through bibliographic research, where articles and books and document consultation were consulted. In conclusion, the article points out that the urban situation of the Island of Mozambique and mainly of the two cities that compose it, has its genesis in the urbanization process under Portuguese colonial rule. The study also concludes that the Portuguese urbanization process created asymmetries between the two cities, whose consequences are notorious nowadays.